Peningkatan Pembelajaran IPS Menggunakan Model Cooperative Learning Tipe Numbered Heads Together di Sekolah Dasar - Pratiwi, Yessi Rosa; Abidin, Zainal; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This  research is to describe the application of the Cooperative Learning TipeNumbered Heads Together (NHT) model to improve student learning outcomes in social studies learning. This research is a classroom action research that uses qualitative and quantitative approaches. The subjects of this research were 28 teachers and fourth grade students. The implementation of this research was carried out in two cycles with research procedures consisting of planning, implementation, observation, and reflection. The results of research was improve a) RPP cycle I 85,7% and cycle II 92,8%. b) Implementation of teacher aspects and aspects of students cycle I 80,6% and cycle II 95,4%,  c) Student learning outcomes cycle I 77,8 and cycle II 89. Thus, the application of the Cooperative Learning TipeNumbered Heads Together (NHT) model can improve learning outcomes students in social studies learning in Grade IV SD Negeri 33 Kalumbuk Kota Padang. Keywords :  Learning outcomes, Social study, NHT